2015
DOI: 10.1088/0034-4885/78/3/036601
|View full text |Cite
|
Sign up to set email alerts
|

Material properties of biofilms—a review of methods for understanding permeability and mechanics

Abstract: Microorganisms can form biofilms, which are multicellular communities surrounded by a hydrated extracellular matrix of polymers. Central properties of the biofilm are governed by this extracellular matrix, which provides mechanical stability to the three-dimensional biofilm structure, regulates the ability of the biofilm to adhere to surfaces, and determines the ability of the biofilm to adsorb gasses, solutes, and foreign cells. Despite their critical relevance for understanding and eliminating of biofilms, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
122
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(141 citation statements)
references
References 167 publications
0
122
0
2
Order By: Relevance
“…Biofilms produce extensive extracellular polysaccharides (EPS) which presents a physicochemical barrier to the penetration of disinfectants 58 . As such the tolerance of biofilms is thought to be associated with the quenching of disinfectants as they pass through the EPS and due to the presence of slow growing or persistor cells that have reduced susceptibility to many disinfectants and other antimicrobials [59][60][61] . Resistance to disinfectants may also be due to a genetic characteristics acquired either by mutation or by gene exchange 62 .…”
Section: Determining the Source Of Infections Related To Hcusmentioning
confidence: 99%
See 1 more Smart Citation
“…Biofilms produce extensive extracellular polysaccharides (EPS) which presents a physicochemical barrier to the penetration of disinfectants 58 . As such the tolerance of biofilms is thought to be associated with the quenching of disinfectants as they pass through the EPS and due to the presence of slow growing or persistor cells that have reduced susceptibility to many disinfectants and other antimicrobials [59][60][61] . Resistance to disinfectants may also be due to a genetic characteristics acquired either by mutation or by gene exchange 62 .…”
Section: Determining the Source Of Infections Related To Hcusmentioning
confidence: 99%
“…Whilst enhanced disinfection may fail to eradicate NTM in water or biofilm phase, Schreiber et al, found that aerosolised M. chimaera were not detectable in brand new HCUs that were undergoing the manufacturer recommended enhanced disinfection regime, 60 suggesting that the infection risk via this route may have been reduced. To date there has been no detailed investigation of risk to patients in terms of the number of M. chimaera in the water phase compared to the number present in aerosols which would have assisted in the establishment of a risk assessment based on quantifiable results.…”
Section: Efficacy Of Decontamination Assessed By Microbiological Testingmentioning
confidence: 99%
“…La expresión de las estructuras de adhesión celular, incluyendo el pili, está sobre regulada para permitir una interacción permanente más fuerte. Una vez unidas, las bacterias comienzan a proliferar y secretar una matriz extracelular compuesta de polisacáridos, ácidos nucleicos y proteínas quedando protegidas de factores nocivos del ambiente (Billings et al, 2015;Santajit & Indrawattana, 2016). La matriz extracelular que encapsula a la biopelícula crea una barrera de difusión física (Jefferson et al, 2005;Singh et al, 2010), que protege a la comunidad bacteriana de la respuesta inmune del hospedador, dificulta o impide la acción antibiótica y otorga alta adherencia del microorganismo a una determinada superficie (Sager et al).…”
Section: Mecanismos De Resistencia Bacteriana a Nivel Extracelularunclassified
“…Their mechanical properties are complex and specially adapted to support survival, with a primary function to prevent detachment from a surface under shear flow conditions. 4,27,33,40,43 The biofilm viscosity is an important property from the perspective of biofilm spreading (contamination) across surfaces, 8 streamer formations, 9,26,46 and biofilm cohesivity. 10 Biofilm viscosity has also been noted to affect bacteriophage penetration through Pseudomonas aeruginosa.…”
Section: Introductionmentioning
confidence: 99%
“…7,8,44 However, until now no correlated fluctuation measurements have been undertaken, to ensure that the long-range properties are being measured, 24 which could help resolve the discrepancies in microrheology results. 4 Most recently, a semi-empirical approach using a two-layer model of biofilms growing in microchannels has been demonstrated as a method to monitor time-varying viscosity. The technique was applied to follow biofilm development in time under different ionic strengths but required an estimation of biofilm height based on indirect measurements and a calibration method using transmission microscopy.…”
Section: Introductionmentioning
confidence: 99%